2019
DOI: 10.1103/physrevmaterials.3.074408
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic temperature-field phase diagram of single crystalline βLi2IrO3 : Magnetization, specific heat, and Li7

Abstract: Detailed magnetization, specific heat, and 7 Li nuclear magnetic resonance (NMR) measurements on single crystals of the hyperhoneycomb Kitaev magnet β-Li2IrO3 are reported. At high temperatures, anisotropy of the magnetization is reflected by the different Curie-Weiss temperatures for different field directions, in agreement with the combination of a ferromagnetic Kitaev interaction (K) and a negative off-diagonal anisotropy (Γ) as two leading terms in the spin Hamiltonian. At low temperatures, magnetic fields… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 38 publications
(88 reference statements)
10
60
0
Order By: Relevance
“…Importantly, our semiclassical results show further that, for H c, the magnitude of the magnetization jump at H * c is significantly reduced by quantum fluctuations, almost to the point that there is no visible change, including the overall slopes of the curves below and above H * c . This renders the detection of this feature in magnetization measurements more challenging and probably explains the absence of the kink in recent measurements [24]. The detection is even more challenging for powder samples given that m c m b .…”
Section: Magnetization Process and The Effect Of Quantum Fluctuationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, our semiclassical results show further that, for H c, the magnitude of the magnetization jump at H * c is significantly reduced by quantum fluctuations, almost to the point that there is no visible change, including the overall slopes of the curves below and above H * c . This renders the detection of this feature in magnetization measurements more challenging and probably explains the absence of the kink in recent measurements [24]. The detection is even more challenging for powder samples given that m c m b .…”
Section: Magnetization Process and The Effect Of Quantum Fluctuationsmentioning
confidence: 99%
“…Remarkably, all experimental data reported so far for Kitaev materials show that their response to the magnetic field depends very strongly on its direction. This is true for the layered compounds Na 2 IrO 3 [10], α-Li 2 IrO 3 [46], and α-RuCl 3 [29][30][31]47], as well as for the three-dimensional (3D) iridates β-Li 2 IrO 3 [21,24] and γ-Li 2 IrO 3 [19,48]. Here we revisit the case of the hyper-honeycomb β-Li 2 IrO 3 and show that its strongly anisotropic response signifies a large separation of energy scales between the relevant microscopic interactions, and can thus be used to extract information about the relative strength of these interactions in a direct way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these materials exhibit complex long-range magnetic orders at sufficiently low temperatures, indicating that other subdominant interactions between magnetic moments are present and may also have nontrivial bond-dependent character. Both experiment [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and theory [27][28][29][30][31][32][33] have shown that these orders are fragile and can be efficiently suppressed by external magnetic field. It was also found that the competition between the external field and anisotropic bond-dependent exchange interactions gives rise to highly anisotropic magnetization processes and a variety of complex orders at intermediate fields [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the purpose of this paper is to understand the recent torque measurements in β-Li 2 IrO 3 [26] and γ -Li 2 IrO 3 [12,13]. These two materials appear to have closely related local energetics [35], and we will therefore focus entirely on the hyperhoneycomb β-Li 2 IrO 3 [23][24][25][26]36,37], whose microscopic minimal model, the nearest-neighbor (NN) J-Kmodel, has been better understood [30,31,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%